Prevention and Control of Hydrogen Sulphide Accidents in Mining Extremely Thick Coal Seam: A Case Study in Wudong Coal Mine - Xuchao Huang; Enmao Wang; Gang Wang; Jiuyuan Fan (Geofluids)
Hydrogen sulphide is a toxic gas often present in coal seams and seriously threatens the lives and health of underground workers in coal mines. In this study, we theoretically modelled hydrogen sulphide generation in extremely thick underground coal mines with the +575 level #45 coal seam of Wudong Coal Mine as an example and obtained the on-site hydrogen sulphide emission pattern and spatial distribution features by combining field measurements and computational fluid dynamics simulation. The results showed that hydrogen sulphide mainly exists in the coal porous system in an adsorbed state. Because hydrogen sulphide has a molecular weight greater than the average molecular weight of air molecules, its concentration decreases with the increase of altitude to the bottom plate. When mining the upper stratified coal stratum, it diffuses widely in the working space; while when mining the lower coal stratum, it mainly concentrates at the bottom of the working face. Based on these analyses, on-site treatments were carried out using mixtures with different concentrations of sodium carbonate and sodium bicarbonate. In addition, different combinations of catalysts as well as type A and type B wetting agents were also tested. Eventually, a neutral KXL-I absorbent was developed, and the process of preinjecting absorbent and spraying absorbent was designed. The results showed that the newly developed KXL-I absorbent has high hydrogen sulphide absorption ability and is suitable for use as an absorbent in Wudong Coal Mine; preinjecting and spraying the absorbent can effectively prevent hydrogen sulphide disasters in the +575 level #45 coal seam in Wudong Coal Mine with the optimal final concentration of 0.9% and the absorption rate of 87% at the shearer of 66.6% at the support. Overall, our study provides valuable information for the prevention and control of hydrogen sulphide disasters in coal mines.